(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Nanotechnology has emerged as an innovative approach in pharmaceutical sciences by improving the delivery of drugs to specific target sites. Nanoparticles such as liposomes, polymeric nanoparticles, dendrimers, solid lipid nanoparticles, and nanoemulsions enhance drug solubility, stability, and bioavailability while reducing systemic side effects. This technology enables controlled and sustained drug release, improving therapeutic effectiveness and patient compliance. Nanotechnology is widely used in the treatment of cancer, infectious diseases, cardiovascular disorders, and neurological conditions by facilitating targeted delivery and minimizing damage to healthy tissues. It also plays an important role in developing personalized medicine and advanced drug delivery systems. Recent advances in nanocarriers have enabled the delivery of poorly water-soluble drugs, proteins, peptides, genes, and vaccines with greater precision and efficacy. In addition, multifunctional nanoparticles capable of simultaneous diagnosis and therapy (theranostics) are opening new avenues for precision medicine. Ongoing research is focused on developing biocompatible and biodegradable nanomaterials with improved safety profiles and enhanced clinical performance. Despite its numerous advantages, challenges such as high production costs, large-scale manufacturing, potential toxicity, long-term safety concerns, and regulatory issues remain barriers to widespread clinical application. Continued research, interdisciplinary collaboration, and technological advancements are expected to establish nanotechnology as a cornerstone of future pharmaceutical drug delivery, leading to safer, more effective, patient-centric, and targeted therapeutic strategies.